Whiplash-Associated Disorders. Biopsychosocial Profiles of Pain Perception in Forensic Cases of Victims of Motor Vehicle Accidents - Pina, David; Puente-López, Esteban; Ruiz-Hernández, José Antonio; Ruiz-Cabello, Aurelio Luna; Aguerrevere, Luis; Magalhães, Teresa (Frontiers in Psychology, 2021)
In order to make a complete diagnosis of all the factors influencing whiplash associated disorders (WAD), the evidence suggests that the condition evaluation should follow an integrated biopsychosocial model. This perspective would offer a fuller view of it, recognizing the interplay between the medical, biomechanical, social, and psychological factors. Despite the progress made in the subject, evidence of which psychosocial factors influence the experience of pain in litigant WAD patients is limited. A cross-sectional design and a cluster analysis was used to study the experience of pain and the psychosocial factors included therein in 249 patients with WAD assessed after suffering a motor vehicle accident. Three clusters were obtained: C1, with low scores of pain and a slight-moderate alteration of the Health-Related Quality of Life (HRQoL); C2, with medium scores of pain, alteration of HRQoL and a perception of moderate disability; and C3, with medium-high scores of pain, alteration of the HQoL, perception of moderate disability, presence of anxious-depressive symptomatology, poorer comprehension of the condition suffered, and the belief that it will extend over a long period of time. The results show a heterogeneous experience of pain in WAD, compatible with the biopsychosocial model of disease and the multidimensional approach to pain. The role of the psychologist in the evaluation of the condition could be useful to obtain a complete view of the condition, thus ensuring that the treatment is adapted to the needs of the patient.